Does rivalry matter? An analysis of sport consumer interest on social media. Issue 4 (6th August 2019) - Watanabe, Nicholas Masafumi; Pegoraro, Ann; Yan, Grace; Shapiro, Stephen L.
Abstract : Purpose: Previous research on rivalry games in sport has predominantly focused on understanding the nature of these games and their effects on consumer behavior. As such, the purpose of this paper is to conduct an empirical examination to provide better theoretical and empirical understanding of how rivalries may impact the posting of content online. Design/methodology/approach: This research utilizes Twitter data measuring the number of posts by individuals about college football teams to model how often fans create content during game days. The models in this study were estimated using fixed-effects panel regressions. Findings: After controlling for a number of factors, including the type of rivalry game, results indicate fans post more during traditional rivalries. Furthermore, newer rivalry games had less impact on the amount of content posted about a team. Practical implications: The findings from this research provide sport marketers with important information regarding fan use of digital platforms. Notably, the results suggest rivalries can help to boost the volume of content individuals post about a team, indicating these games provide teams with an opportunity to maximize their engagement with fans and focus on key marketing objectives. Originality/value: To date, there has been little examination considering whether rivalries affect behaviors in the digital realm. Therefore, the current investigation is one of the first studies to examine how rivalries impact social media behavior.